A New Model on Mixed Reality for 3 Dimensional (3D) Geospatial Terrain in Enhancing the Situational Awareness amongst Military Decision Makers’ - Wahab, Norshahriah Binti; Narjun, Nur Syuhada Binti Muhamad; Ramli, Suzaimah; Zainudin, Norulzahrah Mohd; Hasbullah, Nor Asiakin; Afiza, Mat Razali Noor; Isa, Mohd Rizal Mohd (International Journal of Engineering and Technology, 2018)
Decision making process in military require military who are capable and highly skilled of having a complete set of skills in making decision as well as situational awareness (SA). However, the ability and skills the decision maker have are not sufficient without an efficient and effective interaction and control between the equipment and decision maker in conducting an operation. In this day and age, people are exposed to mixed reality concept in line with the growth of software application technology where people started to demand on their needs for applications used. In fact, software application have shown a rapid development in computing technology world regarding processing power, memory capacity and battery life simultaneously with the new technology supplied such as improvement of the connectivity, external peripherals, GPS and location-based services. This paper proposes the implementation of mixed reality technology specifically in design on 3 Dimensional (3D) geospatial terrain to conduct the military decision making in an operation. The research was carried out to determine the appropriate elements and features of mixed reality for this application consists of anything containing pure or virtual elements, mixed reality space and interaction, reaction, and interaction within 3D mixed reality object. This mixed reality application is considered to provide an effective and efficient 3D map that can interact and control for military operation. Usability testing is selected to conduct the experiment in an open area, assigning the test participants as clients and the evaluator to observe and collect data from the participants. In summary, the research proposes a mixed reality for 3 Dimensional (3D) geospatial terrain in enhancing the situational awareness amongst military decision makers’.